The Impairment of Food Patterns in Venezuela: Preliminary Results from the Latin American Study of Nutrition and Health (ELANS) –Venezuelan Chapter - Ramírez Narváez, Guillermo José (2017)
Background The Venezuelan Study of Nutrition and Health is part of ELANS, a multicenter study conducted in 8 Latin American countries. Venezuela, presented a food shortage situation during 2015. The objective was to identify and analyze the existing food patterns (FP) observed within the population during 2015. Methodology Cross sectional study of a representative sample of 1132 subjects. Food and beverages consumption was recorded in two household’s visits using 24 hour recalls. The food and beverages intake was transformed into energy, macronutrients and micronutrients values using the Nutrition Data System for Research version 2013 software. Hotelling T 2 Test was made to identify differences between genders, age groups, and macronutrient groups. Principal Component Analysis (PCA) was performed for obtaining the food patterns and non-parametric tests to identify food patterns by socioeconomic level. Results Women average caloric intake was 1749.1 Kcal/day and men 2059 Kcal/day, 85.3% of men are caloric deficient compared to 72.8% women in deficit. Daily intake of macronutrient diminishes significantly at older ages in women (p<0.05). Lambda Wilks analysis shows an effect showing that at older ages lower intakes of fat. PCA showed the existence of five food patterns. FP1 (wealthiest) was reported by 6.1% of the population, FP2 by 17.3%, FP3 by 22.0%, FP4 by 19.2% and FP5 (poorest) by 35.4%. Only FP1 covered the Venezuelan caloric recommendations. Conclusions 93.9% of Venezuelan population exhibited in 2015 a FP that do not cover the established requirements, further research is recommended to establish whether underreporting can be contributing to this inadequacy.